Effect of omeprazole and cimetidine on prepyloric gastric ulcer: double blind comparative trial. Issue 2 (February 1988) - Lauritsen, K; Rune, S J; Wulff, H R; Olsen, J H; Laursen, L S; Havelund, T; Astrup, L; Bendtsen, F; Linde, J; Bytzer, P
Abstract : We conducted a six week double blind randomised study of 176 patients with prepyloric gastric ulcer to determine whether the proton pump inhibitor, omeprazole 30 mg daily would accelerate healing and pain relief, as compared with cimetidine 1 g daily. At two, four, and six weeks after entry ulcers healed in a larger percentage of patients treated with omeprazole (54, 81, and 86%) than of those treated with cimetidine (39, 73, and 78%) ('intention to treat' cohort; p less than 0.05 at two weeks). A higher proportion of patients on omeprazole became free of pain during the first week of treatment (p less than 0.05). No major clinical or biochemical side effects were noted. Omeprazole is an efficient treatment for patients with prepyloric gastric ulcers.